Pengalaman Mahasiswa dalam Mengimplementasikan Kurikulum Merdeka Pada Matakuliah Micro teaching - Prastowo, Aang Yudho (Jurnal Ilmiah Dikdaya, 2023)
Higher Education up to participating in teacher professional education. At the Higher Education level, prospective teachers or students carry out exercises in carrying out learning or learning practices. Practical activities are carried out with a small scope or often called micro teaching. Micro teaching helps students develop teaching skills. Teaching ability cannot be separated from the curriculum. Therefore, to produce professional teacher candidates, it is necessary to train students in the implementation of the curriculum used, where the current curriculum used is the independent curriculum. This research is aimed at knowing students' experiences in implementing the independent curriculum. The research conducted was a survey with a quantitative descriptive method. This research method is based on survey results. Data collection technique with a questionnaire. Data analysis techniques by processing the data obtained expressed in percentages and then analyzed descriptively. Based on the results of the analysis, it can be concluded (1) that most micro teaching students have the ability to develop teaching modules. Improvements to student weaknesses lie in the difficulty of finding models, methods, learning strategies, exercises, meaningful understanding, assessment, enrichment and glossaries. (2) the implementation of independent curriculum learning that has been carried out by students by applying differentiation learning, needs to pay attention to aspects of the implementation of differentiation learning itself, namely (a) student readiness, interests and learning styles, (b) content preparation, and (c) learning environment and learning products